FEATURES OF THE FORMATION OF IMITATION OF SPEECH IN CHILDREN WITH ALALIA SPEECH DEFECTS - Vokhobova Munirakhan Sadirdinovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the features of the formation of speech mimicry in children with alalia speech impairment and on the formation of speech mimicry in children with Motor alalia.